Species composition and natural infectivity of anthropophilic Anopheles (Diptera: Culicidae) in the states of Córdoba and Antioquia, Northwestern Colombia (2009)
ABSTRACT : Malaria is a serious health problem in the states of Córdoba and Antioquia, Northwestern Colombia, where 64.4% of total Colombian cases were reported in 2007. Because little entomological information is available in this region, the aim of this work was to identify the Anopheles species composition and natural infectivity of mosquitoes distributed in seven localities with highest malaria transmission. A total of 1,768 Anopheles mosquitoes were collected using human landing catches from March 2007-July 2008. Ten species were identified; overall, Anopheles nuneztovari s.l. was the most widespread (62%) and showed the highest average human biting rates. There were six other species of the Nyssorhynchus subgenus: Anopheles albimanus (11.6%), Anopheles darlingi (9.8%), Anopheles braziliensis (6.6%), Anopheles triannulatus s.l. (3.5%), Anopheles albitarsis s.l. and Anopheles oswaldoi s.l. at < 1%; and three of the Anopheles subgenus: Anopheles punctimacula, Anopheles pseudopunctipennis s.l. and Anopheles neomaculipalpus at < 1% each. Two species from Córdoba, An. nuneztovari and An. darlingi, were found to be naturally infected by Plasmodium vivax VK247, as determined by ELISA and confirmed by nested PCR. All species were active indoors and outdoors. These results provide basic information for targeted vector control strategies in these localities.